2022
DOI: 10.1111/iju.14795
|View full text |Cite
|
Sign up to set email alerts
|

Supervised machine learning algorithm identified KRT20, BATF and TP63 as biologically relevant biomarkers for bladder biopsy specimens from interstitial cystitis/bladder pain syndrome patients

Abstract: Objectives This study was carried out to identify biomarkers that distinguish Hunner‐type interstitial cystitis from non‐Hunner‐type interstitial cystitis patients. Methods Total ribonucleic acid was purified from 212 punch biopsy specimens of 89 individuals who were diagnosed as interstitial cystitis/bladder pain syndrome. To examine the expression profile of patients’ bladder specimens, 68 urothelial master transcription factors and nine known markers (E‐cadherin, cytokeratins, uroplakins and sonic hedgehog)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…1 The finding of reduced KRT20 in NHIC vs HIC bladder mucosa in this study was in line with that reported previously by Kuo's group, whereas they demonstrated that the expression levels of P63 proteins encoded by the TP63 gene was reduced in HL-adjacent mucosa compared with NHIC or control healthy mucosa (ref #7 of this paper), which was not detected in the gene expression levels in this study. 1 However, the results of these biomarker studies are totally dependent on how accurately the cystoscopic diagnosis was made to identify HL in the first place. As discussed in the supplementary discussion of this study, the machine learning algorithm cannot replace the cystoscopy diagnosis of HL.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…1 The finding of reduced KRT20 in NHIC vs HIC bladder mucosa in this study was in line with that reported previously by Kuo's group, whereas they demonstrated that the expression levels of P63 proteins encoded by the TP63 gene was reduced in HL-adjacent mucosa compared with NHIC or control healthy mucosa (ref #7 of this paper), which was not detected in the gene expression levels in this study. 1 However, the results of these biomarker studies are totally dependent on how accurately the cystoscopic diagnosis was made to identify HL in the first place. As discussed in the supplementary discussion of this study, the machine learning algorithm cannot replace the cystoscopy diagnosis of HL.…”
supporting
confidence: 93%
“…However, the results of these biomarker studies are totally dependent on how accurately the cystoscopic diagnosis was made to identify HL in the first place. As discussed in the supplementary discussion of this study, the machine learning algorithm cannot replace the cystoscopy diagnosis of HL 1 . So far, useful biomarkers for the IC/BPS subtype classification that exceed the cystoscopic diagnosis have not been identified.…”
mentioning
confidence: 91%
See 1 more Smart Citation